2019
DOI: 10.1080/19491034.2019.1616507
|View full text |Cite
|
Sign up to set email alerts
|

Plant condensin II is required for the correct spatial relationship between centromeres and rDNA arrays

Abstract: Plants possess the structural maintenance of chromosome (SMC) protein complexes cohesin, condensin, and SMC5/6, which function in fundamental biological processes such as sister chromatid cohesion, chromosome condensation and segregation, and damaged DNA repair. Recently, increasing evidence in several organisms has suggested that condensin is involved in chromatin organizations during interphase. In Arabidopsis thaliana , condensin II is localized in the nucleus throughout interphase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Though positive spatial interactions with www.nature.com/scientificreports/ the nucleolus are unlikely to subtend our observations, the recently reported increased association of centromeric regions with the nucleolus in the nuc1 nucleolin mutant 63 raises the question of whether negative spatial interactions between CCs and the nucleolus may participate to the repulsive organization shown here. Other nuclear factors are likely involved, as suggested for example with recent studies reporting increased centromere association in mutants of plant condensin II subunits 64,65 .…”
Section: An Objective Demonstration Of Chromocenter Peripheral Locatimentioning
confidence: 90%
“…Though positive spatial interactions with www.nature.com/scientificreports/ the nucleolus are unlikely to subtend our observations, the recently reported increased association of centromeric regions with the nucleolus in the nuc1 nucleolin mutant 63 raises the question of whether negative spatial interactions between CCs and the nucleolus may participate to the repulsive organization shown here. Other nuclear factors are likely involved, as suggested for example with recent studies reporting increased centromere association in mutants of plant condensin II subunits 64,65 .…”
Section: An Objective Demonstration Of Chromocenter Peripheral Locatimentioning
confidence: 90%
“…CAP-D2 and CAP-D3 prevent the association of centromeres and induce chromatin compaction (Schubert et al, 2013). The requirement of the condensin II-specific subunits CAP-H2 and CAP-G2 for keeping centromeres apart has been confirmed by Sakamoto et al (2019). In addition, these authors showed that condensin II is necessary for the correct spatial arrangement between centromeres and rDNA arrays.…”
Section: Introductionmentioning
confidence: 91%
“…3D). Furthermore condensin-2 has been recently implicated in controlling the association and dissociation of centromeres 65 . Additionally, we find an Fst outlier peak over CPg36347, homologue of DAYSLEEPER, an essential domesticated transposase 66 .…”
Section: Selective Sweeps Associated Specifically With Wgdmentioning
confidence: 99%